RANCANG BANGUN TIMER KONTROL ALAT LAMPU ULTRA VIOLET STERILIZER DILENGKAPI SISTEM BUZZER - Novriani Romaulina Saragih; Rizaldi Ibrahim (JURNAL MUTIARA ELEKTROMEDIK, 2018)
Ultraviolet lamp sterilizer is a hospital operating room sterilizer to avoid spore living species, as well as contaminated bacterial viruses from outside where by utilizing S. ultraviolet light type. Planning of this tool aims to obtain a design timer for ultraviolet lamp sterilizer equipped with a system ATMega8535 microcontroller based buzzer uses PIR sensor as an indicator of detecting objects in the operating room. Where this research begins with gathering resources, formulating problems, designing tools, designing tools, and performing function tests. After the device has been designed, the function test is performed for each circuit in the tool to work properly, where by measuring each circuit on the device to find out whether the device works according to a good system where by measuring power supply voltage, PIR sensor, ultraviolet lamp, relay, and buzzer.